(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Ludmila I. Bronskaya, Irina N. Ivanova (Stavropol, Russian Federation) A classic text always gives rise to various interpretations and most assuredly such profound and monumental one as the novel by M.A. Bulgakov. Despite decided success of contemporary Bulgakov scholars, it cannot be claimed that investigation of the novel’s philosophy and ontology is completed. To our opinion, one of the most interesting possible interpretations of the text is not its evaluation in terms of canonicity/noncanonicity of Yeshua and indisputable “heterodoxness” from the viewpoint of Orthodox Church, but an attempt to find other spiritual traditions in the novel, polemical or parallel to Orthodox Christianity, especially gnostic traditions and motives. Thus, gnostic sources of the novel, its space-time structure, concept of the individual, traditions of humanism (in reference to the new “socialistic humanism” of the power), motives of Sophia the image of Margarita, mythologeme of the Master and his death still remain unclear. The article suggests an analysis of the great novel’s motive structure in regard to the gnostic myth typified in it. Keywords: gnosticism in literature, Russian literature of the 20 th century, mythopoetics, Bulgakov, tradition, motive. DOI 10.23683/1995-0640-2019-1-186-194